2000
DOI: 10.1128/jvi.74.16.7451-7461.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Gammaherpesvirus 68 v-Cyclin Is a Critical Regulator of Reactivation from Latency

Abstract: Murine gammaherpesvirus 68 (␥HV68; also referred to as MHV68) infection of mice is a developing small-animal model for analysis of gammaherpesvirus pathogenesis (reviewed in references 18, 19, 45, 46, 64, and 69). ␥HV68 is a gamma-2 herpesvirus which is closely related to the human and primate gammaherpesviruses Epstein-Barr virus (EBV), Kaposi's sarcoma-associated herpesvirus (KSHV), and herpesvirus saimiri (HVS) (22,67). Acute ␥HV68 infection of laboratory mice is cleared by 2 to 3 weeks postinfection, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
213
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(227 citation statements)
references
References 72 publications
(53 reference statements)
13
213
1
Order By: Relevance
“…In our model, we found that FITC reactivated transcription of lytic viral RNA in the lungs (although it was to a level two orders of magnitude below peak viral gene expression 5 days after the primary infection [ Figure 5 and data not shown]). To further investigate this question, we infected mice with a mutant strain of gHV-68 (DORF72) with a 100-fold reduced ability to reactivate (15). There is no evidence that infection with DORF72 results in lytic or persistent infection during long-term latency (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our model, we found that FITC reactivated transcription of lytic viral RNA in the lungs (although it was to a level two orders of magnitude below peak viral gene expression 5 days after the primary infection [ Figure 5 and data not shown]). To further investigate this question, we infected mice with a mutant strain of gHV-68 (DORF72) with a 100-fold reduced ability to reactivate (15). There is no evidence that infection with DORF72 results in lytic or persistent infection during long-term latency (33).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this mutation, DORF72 has a greatly diminished ability to reactivate from latency (approximately 100-fold reduction) (15). Mice were inoculated intranasally with 5 3 10 4 PFU of DORF72, 5 3 10 4 PFU of a v-cyclin marker-rescue virus (''MR,'' essentially a wild-type control), or were mock infected with saline on Day 0.…”
Section: Reactivation Of Ghv-68 Is Not Necessary To Augment Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…MEFs were seeded in 200 ml volumes in 96-well plates at a concentration of 5610 4 cells ml 21 in DMEM containing 2.5 % FBS (Invitrogen), L-glutamine, penicillin and streptomycin. Lung cells were resuspended at a concentration of 10 6 cells ml 21 , and LDA was performed as described elsewhere (van Dyk et al, 2000;Weck et al, 1996) with the exception that threefold serial dilutions were made. To determine the levels of preformed lytic virus, a duplicate aliquot of cells was subjected to three rounds of freeze-thawing and lysates were plated in 100 ml volumes onto MEF monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…This insertion removes most of ORF 72, leaving behind only 281 nucleotides at its 3= end, but does not alter ORFs upstream of ORF 72. ␥HV68.OVA replicates with kinetics similar to those of wild-type ␥HV68 in vitro (4), and disruption of ORF 72 via gene insertion does not impair either viral acute replication or establishment of latent infection in vivo (24). (A) OTI-RAG and RAG mice were infected intraperitoneally (i.p.)…”
mentioning
confidence: 99%